The lily of Ludgate Hill - Matthews, Mimi (Belles of London, 2024)
"Fortune favors the bold-but is a confirmed spinster daring enough to loosen the reins and accept a favor from the wicked gentleman who haunts her dreams? Lady Anne Deveril doesn't spook easily. A woman of lofty social standing known for her glacial beauty and starchy opinions, she's the unofficial leader of her small group of equestriennes. Since her mother's devastating plunge into mourning six years ago, Anne voluntarily renounced any fanciful notions of love and marriage. And yet, when fate puts Anne back into the entirely too enticing path of Mr. Felix Hartford, she's tempted to run...right into his arms. No one understands why Lady Anne withdrew into the shadows of society, Hart least of all. The youthful torch he once held for her has long since cooled. Or so he keeps telling himself. But now Anne needs a favor to help a friend. Hart will play along with her little ruse-on the condition that Anne attend a holiday house party at his grandfather's country estate. No more mourning clothes. No more barriers. Only the two of them, unrequited feelings at last laid bare. Finally free to gallop out on her own, Anne makes the tantalizing discovery that beneath the roguish exterior of her not-so-white knight is a man with hidden depths, scorching passions-and a tender heart"--